Inovações técnicas e tecnológicas na construção civil - Bitencourt, Fernando Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This study show the civil construction's history and it details how the evolution of the tools in this sector was. Services that were performed manually and used to require many time and physical effort now are easily performed, requiring less time and performing the services more efficiently with a higher quality standard. In addition, this study show how those tools can contribute to the construction nowadays with quality and saving time and money. Other subject in this study is the quality in the civil construction, where it's shown how those tools contribute with a higher quality standard in constructions, and it can differentiate a company in the market. It's also shown an optimization analysis of a building construction in Guaratinguetá, where it's made a cost-benefit comparison between the traditional techniques that were used and the new shown techniques, which proves the hypotheses that those new tools are economically viable for the construction companies

Essa monografia mostra a história da construção civil, além de detalhar como foi a evolução das ferramentas no setor. Serviços que antes eram feitos de maneira manual e requeriam muito tempo e esforço físico hoje são executados de maneira mais fácil, exigindo menos tempo e executando as tarefas de maneira mais eficiente e com um maior padrão de qualidade. Além disso, o estudo mostra como essas ferramentas podem contribuir para a obra nos dias de hoje, seja pela maior qualidade ou pela economia de tempo e dinheiro gerada. Outro ponto abordado nesse trabalho é a questão da qualidade na construção civil, onde é mostrado como e quanto essas ferramentas contribuem para um maior padrão nas construções, o que pode diferenciar uma construtora no mercado de trabalho. É feita também uma análise de otimização da construção de um prédio na cidade de Guaratinguetá, onde há uma comparação de custo-benefício entre as técnicas tradicionais utilizadas e as novas técnicas apresentadas, comprovando a hipótese de que essas novidades valem a pena financeiramente para as construtoras
Keywords: Construção civil; Ferramentas; Inovações tecnologicas; Building